Leishmania donovani-Induced Increase in Macrophage Bcl-2 Favors Parasite Survival - Pandey, Rajeev Kumar; Mehrotra, Sanjana; Sharma, Smriti; Gudde, Ramachandra Subbaraya; Sundar, Shyam; Shaha, Chandrima (Frontiers in Immunology, 2016)
Members of the Bcl-2 family are major regulators of apoptosis in mammalian cells and hence infection-induced perturbations in their expression could result into elimination of the parasites or creation of a niche favoring survival. In this investigation, we uncover a novel role of host Bcl-2 in sustaining Leishmania donovani infection. A rapid two-fold increase in Bcl-2 expression occurred in response to parasite challenge. Downregulation of post infection Bcl-2 increase using siRNA or functional inhibition using Bcl-2 small molecule inhibitors interfered with intracellular parasite survival confirming the necessity of elevated Bcl-2 during infection. An increased nitric oxide (NO) response and reduced parasitic burden was observed upon Bcl-2 inhibition, where restitution of the NO response accounted for parasite mortality. Mechanistic insights revealed a major role of elevated Th2 cytokine IL-13 in parasite induced Bcl-2 expression via the transcription factor STAT-3, where blocking at the level of IL-13 receptor or downstream kinase JAK-2 dampened Bcl-2 induction. Increase in Bcl-2 was orchestrated through TLR-2-MEK-ERK signaling and changes in TLR-2 levels affected parasite uptake. In a mouse model of visceral leishmaniasis (VL), Bcl-2 inhibitors partially restored the anti-microbial NO response by at least two-fold increase that resulted in significantly reduced parasite burden. Interestingly, monocytes derived from the peripheral blood of six out of nine human VL subjects demonstrated Bcl-2 expression at significantly higher levels and sera from these patients showed only marginally quantifiable nitrites. Collectively, our study for the first time reveals a pro-parasitic role of host Bcl-2 and the capacity of host-derived IL-13 to modulate NO levels during infection via Bcl-2. Here, we propose Bcl-2 inhibition as a possible therapeutic intervention for VL.